Strategic ownership configurations to foster intangible cultural heritage in Japanese football events - Gúdel, Ricardo; Hernández-Correa, Emilio; Acebes, Fernando; Pajares, Javier (Frontiers in Sports and Active Living, 2025)
IntroductionThis study examines how different configurations of the Ownership Landscape influence the preservation of Intangible Cultural Heritage in sporting events, using Japan as a case study. Drawing on the Resource-Based View, it explores how ownership models act as strategic resources that affect both cultural sustainability and long-term competitiveness.MethodsA qualitative multiple-case study was conducted on four football-related events: the J.League, the All Japan University Football Championship, the Shakaijin Cup, and local festival-based tournaments. The study combined documentary analysis with Data Envelopment Analysis to assess how governance and ownership structures generate valuable, rare, inimitable, and non-substitutable resources.ResultsFindings reveal that participatory and hybrid ownership models are more effective in activating VRIN resources, ensuring both organizational resilience and cultural embeddedness. A blend of national sponsorship and local identity in professional leagues, the academic traditions of the Intercollege, and the Shakaijin Cup's regional roots show how sporting events reflect and generate cultural forms.DiscussionThis research challenges top-down and purely economic evaluations of sports events, advocating for culturally sensitive governance that fosters local engagement and authenticity. It extends the RBV to multi-actor, culturally embedded ecosystems and proposes adaptable principles: promoting hybrid ownership, embedding cultural narratives, and engaging diverse stakeholders. Sporting events, when aligned with community values, serve as platforms for intergenerational cultural transmission and community development.